Analysis for inventory management of a fast fashion company - Huang, Mufeng (2019)
With the continuous development of global integration, a large number of famous apparel companies enter the Chinese market, and the competition in the apparel industry is extremely fierce. In recent years, China's garment industry has been overstocked, operating efficiency has declined, and inventory management problems have affected many business operators. With the characteristics of the apparel products with uncertain demand and large fluctuations, apparel enterprises are faced with the problem of inventory backlog. In this environment, improving the demand forecast level of products, optimizing inventory management, and reducing inventory costs have become effective means for enterprises to enhance market competitiveness.